2021
DOI: 10.1097/pas.0000000000001850
|View full text |Cite
|
Sign up to set email alerts
|

Metatypical Adenoid Cystic Carcinoma

Abstract: Adenoid cystic carcinoma is a malignant salivary gland neoplasm, commonly involving the major and minor salivary glands. Adenoid cystic carcinoma arising in the skull base region is considerably less common and is characterized by aggressive clinical behavior, perineural invasion, and intracranial extension. Classically, these tumors are composed of ductal and myoepithelial cells, arranged as tubules and cribriform structures, as well as in a solid pattern when higher in grade. The distinctive molecular findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…11 These were recognized as a significant pitfall with other tumors that more typically show these morphologies, and were proven with the finding of canonical MYB::NFIB and MYBL1:: NFIB fusions in these cases. 11 Anecdotally, many head and neck experts have suggested that nonmajor gland sites may The tubular hypereosinophilia was also seen with canonical fusions and cases that were negative for fusions. A variety of morphology was seen including rhabdoid luminal cells (A) in case 15, a MYBL1::NFIB-positive laryngeal tumor; complex micropapillary and luminal-cribriform growth in case 13, a MYB::NFIB-sive maxillary tumor (B); and solid squamoid growth in case 9, a fusion negative tumor (C).…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…11 These were recognized as a significant pitfall with other tumors that more typically show these morphologies, and were proven with the finding of canonical MYB::NFIB and MYBL1:: NFIB fusions in these cases. 11 Anecdotally, many head and neck experts have suggested that nonmajor gland sites may The tubular hypereosinophilia was also seen with canonical fusions and cases that were negative for fusions. A variety of morphology was seen including rhabdoid luminal cells (A) in case 15, a MYBL1::NFIB-positive laryngeal tumor; complex micropapillary and luminal-cribriform growth in case 13, a MYB::NFIB-sive maxillary tumor (B); and solid squamoid growth in case 9, a fusion negative tumor (C).…”
Section: Discussionmentioning
confidence: 84%
“…All of these findings, however, have recently been described in M-AdCC occurring in the sinonasal tract and skull base 11. These were recognized as a significant pitfall with other tumors that more typically show these morphologies, and were proven with the finding of canonical MYB::NFIB and MYBL1::NFIB fusions in these cases 11. Anecdotally, many head and neck experts have suggested that nonmajor gland sites may show more variation in morphology (personal observations of the authors).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations